Analyzing University Students’ Attitude And Behavior Towards Jesi Program Using Technology Acceptance Model - Obenza, Brandon N.; Galido, June Clyde A.; Madridano, Tristan John M.; Mocallay, Kris Bryan V.; Quio, Kenta; Rojo, Erika Mae H.; Sedot, Jilian C. (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This study aimed to examine university students’ attitudes and behavioral intentions toward the JESI Interactive Learning Module using the Technology Acceptance Model (TAM), focusing on perceived ease of use and perceived usefulness. Methodology: A structured 5-point Likert scale questionnaire adapted from Davis (1989) was distributed via Google Forms. A total of 269 university students were selected using stratified random sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0 and descriptive statistics via Jamovi software. Main Findings: The findings revealed that PU (β = 0.495, p < 0.000) has significant direct effects toward attitude, while PEOU (β = 0.117, p < 0.144) has no significant direct effects toward attitude. Additionally, attitude (β = 0.594, p < 0.00) has also been found to have a significant direct effect toward behavioral intention to use. Additionally, the structural model demonstrated a good-fit in all PLS-SEM indices. Novelty/Originality of this study: This study is the first to apply TAM to evaluate JESI, a context-specific ILM in Philippine higher education. It advances theoretical understanding of technology acceptance and offers practical insights for improving ILM design and adoption across similar digital platforms in higher education institutions.